La construcción discursiva de la mala fama de la prejubilación entre los mineros. Imágenes de rechazo y hechos del contexto social. - García García, José Luis (Revista de Antropología Social, 2006)
This article analyzes the context and the discursive process by which the collective category of the early retiree is constructed in Asturian mining communities. Departing from the legal ambiguity and hence social ambiguity of these personages and status the essay studies the discursive construction of ill repute in respect to them and as a way of giving meaning to a newly created social collective difficult both to define and accept in normal social interaction. Differently than other discourses that circulate about ill repute in respect to the individuals, those concerning the collective category are rhetorical in their construction and in their social use. Their performative value contributes to the social integration and meaning of a defamed category of persons who are basically defined by their unusual use of time and by their lacking in fulfillment of the prescribed social obligations that would normally bind them to their community throughout their working lives.